Quantitative Analysis of Flavonoid Content, Total Phenolic and Toxicity Test of Extract Smilax rotundifolia Leaves From Papua - Appa, Felycitae E.; Tobi, Claudius H.B.; Suprapti, Kevry; Bakri, Nur F.; Barus, Andre A.; Pratiwi, Mustika E. (Jurnal Biologi Papua, 2025)
This study investigates Bungkus leaf (Smilax rotundifolia), a well-known plant in Papua commonly referred to as the three-finger leaf. Indigenous Papuans traditionally use this plant to enlarge genitals, buttocks, and breasts, as well as to treat syphilis. The plant is known to contain flavonoid and phenolic compounds with pharmacological activity. This study aimed to determine the total flavonoid and total phenolic content of the 70% ethanol extract of Bungkus leaf. The research began with simplicia preparation, followed by extraction using 70% ethanol. Qualitative tests, including phytochemical screening and thin-layer chromatography (TLC), were conducted, followed by quantitative analysis using UV-Vis spectrophotometry. The results showed total flavonoid content of 54.696 mg QE/g ± 0.565 and total phenolic content of 32.908 mg GAE/g ± 0.263. The study concluded that the total flavonoid content was higher than the total phenolic content. Toxicity testing categorized the extract as toxic, with an LC50 value of 442.92 ppm.